Design Enterprise Data Center Infrastructure at Computer Center of Al-Jaderyia Baghdad-University Campus - Mahmoud, Halah Hasan (Al-Nahrain Journal of Science, 2018)
Cloud computing is an emerging computing paradigm. It aims to access and host’s computing services and data over the internet. Access is achieved through web browser, and services are supplied by software running on a cloud platform. Cloud computing implementations can be characterized in two models: Service Models and Deployment Models. Cloud Computing resided in a large data center and is able to dynamically provide servers with the ability to address a wide range of needs. A data center (which is the heart of most companies) is a facility used to house computer systems and associated components, such as telecommunications and storage systems. This work presents a plan to design Enterprise Data Center infrastructure network at computer center that connects Colleges, Institutes and Centers within Baghdad University Campus and meets the requirements of modern data centers.